2002
DOI: 10.1007/bf01463167
|View full text |Cite
|
Sign up to set email alerts
|

The theory of general and ideal plastic deformations of Treasca solids

Abstract: Summary. Ideal plastic deformations have been defined elsewhere as solenoidal smooth deformations in which an eigenvector field associated everywhere with the greatest (major) principal rate of deformation is fixed in the material. For the rigid/perfectly plastic Tresca solid, which satisfies the Tresca yield condition and its associated normality flow rule, it is always possible to find an equilibrium stress field which is compatible with an ideal deformation. Under such conditions all material elements under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The characteristic coordinates are denoted as (α, β). The first equation in (6) corresponds to the α-lines and the second to the β-lines. The ideal flow condition requires that the velocity vector V is tangent to the ξ-coordinate lines (Figure 2).…”
Section: System Of Equations In Characteristic Coordinatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic coordinates are denoted as (α, β). The first equation in (6) corresponds to the α-lines and the second to the β-lines. The ideal flow condition requires that the velocity vector V is tangent to the ξ-coordinate lines (Figure 2).…”
Section: System Of Equations In Characteristic Coordinatesmentioning
confidence: 99%
“…This solution is for Tresca's yield criterion. Papers [5,6] have demonstrated that steady and nonsteady three-dimensional ideal flows exist for the material model comprising this yield criterion and its associated flow rule. Only this material model has been associated with the concept of bulk ideal flows for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Hill (1967), who proposed the name ideal flow, generalized the effort to three-dimensional steady flow. Further extension to non-steady three-dimensional flow was made by Wienecke and Richmond (1997) and Richmond and Alexandrov (2002), but without specific application to forming.…”
Section: Introductionmentioning
confidence: 96%
“…Non-steady ideal membrane flows were then used as the basis of an inverse method for designing sheet forming processes [13]. The general equations of three-dimensional non-steady ideal deformations in a special Lagrangian coordinate system were derived and then specialized to the case of axisymmetric non-steady deformations [14]. Hill has extended the steady rigid-plastic ideal flow to steady elastic incompressible plastic ideal flow, but no specific applications of this theory have been presented [15].…”
Section: Introductionmentioning
confidence: 99%